2022
DOI: 10.1038/s41598-022-07274-5
|View full text |Cite
|
Sign up to set email alerts
|

Portable SA/CMC entrapped bimetallic magnetic fly ash zeolite spheres for heavy metals contaminated industrial effluents treatment via batch and column studies

Abstract: Heavy metals are perceived as a significant environmental concern because of their toxic effect, bioaccumulation, and persistence. In this work, a novel sodium alginate (SA) and carboxymethylcellulose (CMC) entrapped with fly ash derived zeolite stabilized nano zero-valent iron and nickel (ZFN) (SA/CMC-ZFN), followed by crosslinking with CaCl2, is synthesized and applied for remediation of Cu(II) and Cr(VI) from industrial effluent. The characterization of the adsorbent and its surface mechanism for removing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
(66 reference statements)
1
7
0
4
Order By: Relevance
“…A zeólita produzida a partir dos minerais vulcânicos peruanos demonstraram capacidade de troca iônica e adsorção, no qual o modelo cinético de Blanchard de pseudo-segunda ordem e a isoterma de Freundlich melhor se adequaram. Os materiais zeolíticos apresentaram granulometria de 4 mm, obtendo uma remoção de 29,40 mg por grama de zeólita sintetizada por um período de contato de 8 horas Angaru et al (2022) Composto portátil Alginato de Sódio (AS) /Carboximetilcelulose (CMC) em esferas de zeólitas de cinzas volantes magnéticas bimetálicas (ZFN) para o tratamento de efluentes industriais contaminados por metais pesados via lote e coluna.…”
Section: Valdivia Et Al (2021)unclassified
See 3 more Smart Citations
“…A zeólita produzida a partir dos minerais vulcânicos peruanos demonstraram capacidade de troca iônica e adsorção, no qual o modelo cinético de Blanchard de pseudo-segunda ordem e a isoterma de Freundlich melhor se adequaram. Os materiais zeolíticos apresentaram granulometria de 4 mm, obtendo uma remoção de 29,40 mg por grama de zeólita sintetizada por um período de contato de 8 horas Angaru et al (2022) Composto portátil Alginato de Sódio (AS) /Carboximetilcelulose (CMC) em esferas de zeólitas de cinzas volantes magnéticas bimetálicas (ZFN) para o tratamento de efluentes industriais contaminados por metais pesados via lote e coluna.…”
Section: Valdivia Et Al (2021)unclassified
“…O modelo de isoterma de Langmuir, demostram uma melhor adequação aos dados experimentais obtidos na maioria dos artigos, caracterizando-se uma adsorção homogênea e, como já supracitado, a formação de uma monocamada de adsorvato (Zanin et al, 2017;Angaru et al, 2022). No entanto, os experimentos de Taamneh e Sharadqah (2017) e Valdivia et al (2021) apresentaram que o modelo de Freundlich foi o que melhor se ajustou, para uma superfície heterogênea e a formação de mais de uma camada de adsorvato.…”
Section: Cobreunclassified
See 2 more Smart Citations
“…Recently, Angaru et al reported the removal of industrial effluents using sodium alginate (SA) and carboxymethylcellulose (CMC) entrapped with bimetallic magnetic (nano zero valent iron and nickel) fly ash zeolite (ZFN) with the composition of SA : CMC : ZFN at 1 : 1 : 1 (weight ratio). 21,22 The adsorption capacities for Cu( ii ) and Cr( vi ) were found to be 63.29 and 10.15 mg g −1 , respectively. For defluoridation of water different modified zeolites as adsorbents have also been reported.…”
Section: Introductionmentioning
confidence: 99%